1970
DOI: 10.1037/h0029915
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive style and teaching method on categories of achievement.

Abstract: A 2 X 2 factorial design was used to determine the effect of cognitive style and teaching method on three different aspects of subject matter achievement-factual content, conceptual-generalization content, and total content. Data from 80 college subjects indicated that a teacherstructured-presentation method of instruction was significantly superior to an independent-problem-solving method of instruction on all three dependent measures. There was no significant difference between students with an analytic cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
5

Year Published

1972
1972
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
0
13
0
5
Order By: Relevance
“…The guest teachers taught in somewhat different circumstances from that of other field studies reviewed as the ones reported by Sage (1971) and Coop and Brown (1970). Subjects in these studies were college stu dents possibly majoring in the area in which the research was carried out; therefore, more requirements could be placed on performance as note taking and memorization.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The guest teachers taught in somewhat different circumstances from that of other field studies reviewed as the ones reported by Sage (1971) and Coop and Brown (1970). Subjects in these studies were college stu dents possibly majoring in the area in which the research was carried out; therefore, more requirements could be placed on performance as note taking and memorization.…”
Section: Discussionmentioning
confidence: 99%
“…Coop and Brown (1970) used a test with factual and conceptual generalization items, somewhat similar to the achievement device used for this study, and found significant differences in favor of the teacherstructured method of instruction as opposed to the independent problem solving method. Kersh (1958) and others have carried their experiments a stage further than that of the study reported herein in order to test long-term retention and ability to transfer knowledge to a new situation or problem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations